‘I never leave my house without praying’: a qualitative exploration of the psychospiritual experiences of ethnically diverse healthcare staff during the COVID-19 pandemic - Catherine Henshall; Brian Nyatanga; Guy Harrison; Harmandeep Kaur Gill; Juliet Chastney; Riya Patel (BMJ Open)
Objectives The study aimed to understand the psychospiritual experiences and support needs of ethnically diverse healthcare staff during the COVID-19 pandemic.Design A qualitative study using focus groups conducted remotely on Microsoft Teams.Setting The study took place across 10 National Health Service Trusts in England: 5 were Acute Hospital Trusts and 5 were Community and Mental Health Trusts.Participants Fifty-five participants were recruited to the study across 16 focus group meetings. Participants were all National Health Service staff from ethnically diverse backgrounds.Results Psychospiritual concerns were central to participants’ understanding of themselves and their work in the National Health Service. Participants felt there was limited recognition of spirituality within the health service. They described close links between their spirituality and their ethnicities and felt that the psychospiritual support offered within the healthcare setting was not reflective of diverse ethnic and spiritual needs. Improved psychospiritual care was viewed as an opportunity to connect more deeply with other colleagues, rather than using the more individualistic interventions on offer. Participants requested greater compassion and care from leadership teams. Participants described both positive and negative changes in their spirituality as a result of the COVID-19 pandemic.Conclusions Culturally sensitive psychospiritual support is a key aspect of healthcare staff’s well-being, despite identified gaps in this area. Aside from affecting physical, psychological, social and financial aspects of healthcare staff’s lives, the pandemic has also had a significant impact on the ways that people experience spirituality.